British parliamentary papers. Industrial revolution (Irish University Press)
Irish University Press Series of British parliamentary papers. I.U.P. Library of fundamental source books. Editorial dir.: T.P.O.'Neill. Pamphlet volume. 1.Children's employment. Report of the minutes of evidence on the state of children employed in the manufactories of the United Kingdom (1816-397- vol.III [of British parliamentary papers]) together with a report on the employment of boys in sweeping chimneys with minutes of evidence and appendix (1817-400-vol.VI [of British parliamentary papers]). VI, 435 p. - With tabs.